Ethnic Politics in Communist Parties of Nepal - Budha Magar, Bhoj Bikram (Journal of Nepalese Studies, 2025)
This article examines the engagement of Nepal’s communist parties with caste and ethnic politics despite their formal commitment to Marxist class analysis. Classical Marxism treats class relations as the primary basis of social organization, with the economy shaping political, cultural, and religious institutions. In contrast, Communist parties in Nepal have historically prioritized caste and ethnic identities over economic issues. This divergence raises a central question: why and how have caste and ethnic politics become integral to the political practice of Nepal’s Communist parties? The article argues that these parties have substantively departed from their core ideological principles by mobilizing caste and ethnic identities while continuing to present themselves as class-based organizations. The adoption of ethnic agendas by Communist parties remains deeply contested in Nepal. The proliferation of Communist parties has been accompanied by the institutionalization of ethnic organizations within party structures. The Maoist insurgency from 1996 to 2006, which originated in Magar-dominated regions, further demonstrates the strategic mobilization of ethnic grievances. Drawing on PhD fieldwork conducted in Palpa, Pyuthan, and Rolpa between September and December 2018, this article uses field surveys and key informant interviews to analyze both party practices and Magar responses. It concludes by assessing the causes and consequences of ethnic politics within Nepal’s communist movement.